Structure of salts of lithium chloride and lithium hexafluorophosphate as solvates with pyridine and vinylpyridine and structural comparisons: (C5H5N)LiPF6, [p‐(CH2=CH)C5H4N]LiPF6, [(C5H5N)LiCl]n, and [p‐(CH2=CH)C5H4N]2Li(μ‐Cl)2Li[p‐(CH2=CH)C5H4N]2. Issue 3 (13th February 2017) - Jalil, AbdelAziz; Clymer, Rebecca N.; Hamilton, Clifton R.; Vaddypally, Shivaiah; Gau, Michael R.; Zdilla, Michael J.
Abstract : Dissolution of LiCl or LiPF6 in pyridine or vinylpyridine and slow vapor diffusion of this solution with diethyl ether gives solvates of the lithium salts coordinated by pyridine ligands. In the case of the hexafluorophosphate salts, the chemical species formed are similar, namely binary salts with hexafluorophosphate counter‐ions. In contrast, the solvates with LiCl are structurally dissimilar, with one forming a one‐dimensional ionic polymer of fused LiCl rhombs and the other crystallizing as an isolated molecular unit with a complex array of van der Waals interactions of neighboring molecules. Abstract : Due to the flammability of liquid electrolytes used in lithium ion batteries, solid lithium ion conductors are of interest to reduce danger and increase safety. The two dominating general classes of electrolytes under exploration as alternatives are ceramic and polymer electrolytes. Our group has been exploring the preparation of molecular solvates of lithium salts as alternatives. Dissolution of LiCl or LiPF6 in pyridine (py) or vinylpyridine (VnPy) and slow vapor diffusion with diethyl ether gives solvates of the lithium salts coordinated by pyridine ligands. For LiPF6, the solvates formed in pyridine and vinylpyridine, namely tetrakis(pyridine‐κ N )lithium(I) hexafluorophosphate, [Li(C5 H5 N)4 ]PF6, and tetrakis(4‐ethenylpyridine‐κ N )lithium(I) hexafluorophosphate, [Li(C7 H7 N)4 ]PF6, exhibit analogous structures involving tetracoordinated lithium ions with neighboring PF6 − anions in the I and Aea 2 space groups, respectively. For LiCl solvates, two very different structures form. catena ‐Poly[[(pyridine‐κ N )lithium]‐μ3 ‐chlorido], [LiCl(C5 H5 N)] n, crystalizes in the P 21 21 21 space group and contains channels of edge‐fused LiCl rhombs templated by rows of π‐stacked pyridine ligands, while the structure of the LiCl–VnPy solvate, namely di‐μ‐chlorido‐bis[bis(4‐ethenylpyridine‐κ N )lithium], [Li2 Cl2 (C7 H7 N)4 ], is described in the P 21 / n space group as dinuclear (VnPy)2 Li(μ‐Cl)2 Li(VnPy)2 units packed with neighbors via a dense array of π–π interactions.